Slow yoga breathing improves mental load in working memory performance and cardiac activity among yoga practitioners - Deepeshwar, Singh; Budhi, Rana Bal (Frontiers in Psychology, 2022)
This study investigated the immediate effect of slow yoga breathing (SYB) at 6 breaths per minute (bpm) on working memory performance and heart rate variability (HRV) in yoga practitioners. Forty healthy male volunteers performed a working memory task, ‘n-back’, consisting of three levels of difficulty, 0-back, 1-back, and 2-back, separately, before and after three SYB sessions on different days. The SYB sessions included alternate nostril breathing (ANB), right nostril breathing (RNB), and breath awareness (BAW). Repeated measures analysis of variance showed a significant reduction in reaction time (ms) in 2-back condition immediately after ANB (-8%), RNB (-8%) and BAW (-5%) practices. Similarly, the accuracy was improved in 0-back condition after RNB (4%), and in 2-back condition after ANB (6%) and RNB (6%) practices. These results suggest that SYB practice enhances cognitive abilities (8-9%) related to memory load and improves the functioning of cardiac autonomic activity, which is required for the successful completion of mental tasks.